THE INFLUENCE OF LEADERSHIP ON NURSE MOTIVATION THROUGH WORKLOAD AS AN INTERVENING VARIABLE AT UNDATA HOSPITAL - Suarsana, I Nyoman; Hasanuddin, Bakri; Mahardiana, Lina (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2024)
This study aims to determine and analyze the influence directly or indirectly (Intervening) of Leadership on Nurse Motivation, and Workload as an intermediate variable. The population consists of 376 nurses at Undata Hospital in Palu City. Of the 376 populations sampled in this study, 194. This research is descriptive and will be analyzed by Structural Equation Model-Partial Least Square (SEM-PLS) analysis. The results showed that (1) Leadership has a direct influence on the Motivation of Undata Hospital Nurses. This is evidenced by the t-count value of 5.198 with a significance value of 0.000 < 0.05, the path coefficient has a positive value of 0.496; (2) the Leadership variable has a direct influence on the Workload of Undata Hospital nurses t-count value of 14.417 with a significance value of 0.000 < 0.05, the path coefficient has a positive value of 0.765 and (3) the Workload variable has a direct influence on the motivation of Undata Hospital nurses has a t-count value of 4.952 with a significance value of 0.000 < 0.05, the path coefficient has a positive value of 0.409. (4) for the indirect influence of leadership variables on motivation through the workload of Undata Hospital nurses has a t-count value of 4.834 with a significance value of 0.000 < 0.05, indirect effects coefficient has a positive value of 0.313.